Recontextualization of BIPA Learning: Innovative Design of Basic Level Teaching Materials Based on Local Wisdom of North Sumatra - Mutia Febriyana; Syamsuyurnita Syamsuyurnita; Nur Sakinah; Silvia Sandi Wisuda Lubis (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The internationalization of Indonesian language learning for foreign speakers (BIPA) requires teaching materials that not only develop linguistic competence but also promote intercultural understanding through contextualized cultural content. However, most existing BIPA materials remain nationally oriented and insufficiently integrate local cultural identities into beginner-level learning. This study aims to develop and examine an innovative design of basic-level BIPA teaching materials through the recontextualization of North Sumatran local wisdom. Employing a Research and Development (R&D) approach using the ADDIE model, the study involved stages of needs analysis, material design, expert validation, revision, and limited implementation. The teaching materials were designed by transforming local cultural elements of North Sumatra, including traditional foods, social practices, local tourism, and cultural expressions, into communicative language-learning contexts suitable for beginner foreign learners. Data were collected through interviews, documentation, validation sheets, and learner response questionnaires, and were analyzed qualitatively and quantitatively. The findings indicate that the recontextualized materials demonstrate strong pedagogical relevance, cultural authenticity, and communicative appropriateness for basic level BIPA instruction. Expert validation results showed that the materials met content, linguistic, and instructional design standards, while learner responses revealed increased engagement and intercultural awareness. This study contributes to the development of culturally responsive BIPA pedagogy by positioning local wisdom not merely as supplementary cultural information but as an integral component of language learning. The study further highlights the importance of recontextualization in constructing meaningful and globally relevant Indonesian language instruction for foreign learners.